The imaginary self-portrait in the poem Roman de la Rose - Peklar, Barbara (Ars et humanitas, 2017)
"Every portrait that is painted with feeling is a portrait of the artist, not of the sitter ... It is not he who is revealed by the painter; it is rather the painter who, on the coloured canvas, reveals himself," explains the painter who created the evolving portrait of Dorian Gray. Guillaume de Lorris, the author of the medieval poem Roman de la Rose, also presents his soul through the character of the ideal lover, so Amans is a kind of self-portrait. But unlike an ordinary self-portrait, this one does not present the author's personality. It is painted with words, and such an ekphrastic image is universal or influences the reader in ways that can be explained by the Iser's readerresponse theory. The poem enables the reader to feel love, and transforms him into the ideal courtly lover. As distinct from a painting, the invisible ekphrastic image in this text surpasses appearances and presents the reader with a hidden side of his soul. The object represented by ekphrasis does not exist in the outer world, therefore in the example examined here the reader's other self is brought into existence. In contrast to a painted self-portrait, which represents the identity of the author, since the picture and the pictured are identical, a word is a sign which refers to something else. A verbal self-portrait which expresses the author's feelings opens itself up to the reader, who has to complete the image with his imagination. This imaginary image then differs from the external appearance, because it reveals the associated feelings, enables the reader to feel what the author feels, and presents the reader with his other self. The imaginary self-portrait thus does not represent the actual self, but the self that is transformed or improved by the art of love.
Keywords: beseda in podoba; fikcija; francoska književnost; Guillame de Lorris; literarne študije; literarni motivi; Narcisov tolmun; pesnitve; poosebitev; srednjeveška književnost; teorija estetskega učinka